A re-examination of choking in sport - Hill, D. M.; Hanton, S.; Fleming, S.; Matthews, N. (European Journal of Sport Science, 2009)
The purpose of this study was to re-examine choking in sport. Using a grounded theory approach (Glaser & Strauss, 1967), qualitative data were gathered from four "experts" of applied sport psychology, who had published within the stress and anxiety literature, and worked extensively with athletes who had performed in highly stressful situations. The experts perceived that the contemporary definitions of choking in sport fail to reflect fully the experiences of "chokers", and created a more detailed definition in response. They considered the choking process to consist of a stress response that culminates in a significant drop in performance - a choke, which psychologically damages the performer. It was also suggested that the choking process and its consequences were moderated by individual differences and type of sport. Accordingly, they recommended interventions that may alleviate choking and, importantly, generated characteristics that can be used to identify a choker. Such findings offer an extended understanding of choking in sport and provide a framework for future ecologically valid research.